Grammatical Spelling and Written Syntactic Awareness in Children With and Without Dyslexia - Van Reybroeck, Marie (Front Psychol, 2020)
Children with dyslexia face persistent difficulties in acquiring not only reading skills but also spelling skills. Among difficulties in spelling, problems in grammatical spelling have been studied very rarely. The goal of the study is to better understand grammatical spelling difficulties in children with dyslexia by assessing written syntactic awareness skills, a linguistic factor that has not been investigated in the context of spelling until now. It is worth noting that while morphological awareness has been well studied in children with dyslexia, only very few studies have focused on syntactic awareness, which is, however, necessary to produce number or gender agreement. Twenty children with dyslexia were matched to typically developing children on both chronological age and on grammatical spelling level. All the children were asked to perform a subject verb agreement grammatical spelling test and a written syntactic awareness test on the same sentences, as well as control measures. Results demonstrated that the children with dyslexia performed equally compared to grammatical spelling matched children in grammatical spelling, whilst they performed less well compared to children of the same age. For syntactic awareness, they were less accurate at identifying the subject of the complex sentences than spelling age matched children, even though both groups were matched in grammatical spelling. These results demonstrate that children with dyslexia face a specific deficit in written syntactic awareness. It highlights how better understanding of the spelling difficulty will better guide treatment.